2023
DOI: 10.3390/nursrep13030083
|View full text |Cite
|
Sign up to set email alerts
|

Degree of Alarm Fatigue and Mental Workload of Hospital Nurses in Intensive Care Units

Abstract: This study aimed to determine the degree of alarm fatigue and mental workload of ICU nurses, and to clarify the relationship between these two variables. A cross-sectional, descriptive research design was used. Data were collected from 90 nurses working in four ICUs in Seoul, Republic of Korea, using a questionnaire determining their degree of alarm fatigue and mental workload. Data were collected from 6 March to 26 April 2021 and were analyzed using a t-test, ANOVA, and Pearson’s correlation coefficient. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…These findings sugest that ICU nurses, despite experiencing alarm fatigue, promptly respond to any alterations in patients’ conditions. These findings are consistent with previous studies [ 37 , 38 ]. However, they contrast with a study conducted in Ireland, where the majority of nurses either disregarded the alarm or exhibited delayed responses when experiencing alarm fatigue [ 39 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…These findings sugest that ICU nurses, despite experiencing alarm fatigue, promptly respond to any alterations in patients’ conditions. These findings are consistent with previous studies [ 37 , 38 ]. However, they contrast with a study conducted in Ireland, where the majority of nurses either disregarded the alarm or exhibited delayed responses when experiencing alarm fatigue [ 39 ].…”
Section: Discussionsupporting
confidence: 94%
“…For example, during morning shifts, the workload on nurses may increase, leading to heightened attention to alarms [ 36 ]. Conversely, in Korea the highest scoring item was “I hear a certain amount of noise in the ward” [ 38 ]. The items with the lowest scores were “I turn off the alarms at the beginning of every shift” and “I regularly readjust the limits of alarms based on the clinical symptoms of patients”.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alarm fatigue is a significant issue for nurses, particularly in ICUs, where they are subjected to a lot of warnings from different equipment and monitoring devices. 3 , 22 Studies have shown that CCNs experience a moderate-to-high level of alarm fatigue, with scores ranging from 29.1 out of 40 to 69.4 out of 100. 8 , 23 This could be attributed to the complex and critical nature of their work, which requires constant monitoring of patients and their equipment.…”
Section: Discussionmentioning
confidence: 99%
“…The high level of alarm fatigue in the present study suggests that additional efforts are needed to enhance alarm management in critical care settings. Other studies have also shown that when alarms go off repeatedly and constantly, nurses become irritable and impatient, 4 , 22 highlighting the importance of addressing alarm fatigue and enhancing alarm management in hospital settings.…”
Section: Discussionmentioning
confidence: 99%